Gmelina arborea: chemical constituents, pharmacological activities and applications - Charu Arora; Vinita Tamrakar (International Journal of Phytomedicine, 2017)
Gmelina arborea (G. arborea) is a bio-prospective plant belonging to family verbenaceae. It is widely used for it’s medicinal properties from ancient times. The present paper comprehensively reviewed the traditional uses, medicinal properties and chemical constituents isolated from G. arborea based on literature reported as well as critical analysis of the research. The present article is aimed to provide information on recent advances and new foundations and direction for further exploring G. arborea for its applications. Pharmacological research reviewed that G. arborea possess various medicinal properties and biological activities including antidiuretic, antidiarrhoeal, antipyretic, antianalgesic, antioxidant, antidiabetic, antihelmintic, antibacterial, antifungal, cardiopotective, insecticidal, antiulcer, gastro-protective, anticancer, antihyperlipidemic and immunomodulatory activity. It has been reported for its applications in treatment of bone fracture, hypertension and regeneration of β-cells. The main chemical constituents of G. arborea include lignans, iridoid glycoside, flavonoids, flavons, flavone glycoside and sterols. The present review provides all the references and beneficial directions to explore further application of G. arborea.